2015
DOI: 10.1074/jbc.m115.661058
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Recruitment of Class IIa Histone Deacetylases (HDACs) to the SMRT/NCoR Transcriptional Repression Complex

Abstract: Background: Class IIa histone deacetylases (HDACs) repress transcription through association with the SMRT/NCOR co-repressor complex.Results: A repeated peptide motif mediates recruitment of class IIa HDACs to the co-repressor proteins interacting adjacent to the active site.Conclusion: Class IIa HDACs are recruited to co-repressors by a simple repeated peptide motif.Significance: First insights into the assembly of Class IIa HDACs with repression complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 35 publications
7
43
1
Order By: Relevance
“…8c). These data confirm a role of the HDAC7 surface zinc binding site in SMRT binding, as also observed in HDAC4 7, 49, 58 .
Figure 8Test of SMRT(1255–1452) binding to the C535A/H541A mutant of HDAC7. ( a ) Intensities of resonance signals of SMRT(1255–1452) residues in 15 N- 1 H HSQC NMR spectra with added 3.6-fold molar excess of the HDAC7 (C535A/H541A) mutant, normalized to corresponding intensities in the HSQC spectrum of free SMRT(1255–1452).
…”
Section: Resultssupporting
confidence: 79%
“…8c). These data confirm a role of the HDAC7 surface zinc binding site in SMRT binding, as also observed in HDAC4 7, 49, 58 .
Figure 8Test of SMRT(1255–1452) binding to the C535A/H541A mutant of HDAC7. ( a ) Intensities of resonance signals of SMRT(1255–1452) residues in 15 N- 1 H HSQC NMR spectra with added 3.6-fold molar excess of the HDAC7 (C535A/H541A) mutant, normalized to corresponding intensities in the HSQC spectrum of free SMRT(1255–1452).
…”
Section: Resultssupporting
confidence: 79%
“…Most HDAC inhibitors lack isoform selectivity and generally consist of a chelating moiety that interacts with the active-site zinc atom, a narrow linker region that spans the catalytic groove and a capping group (Sternson et al, 2001). It has emerged that some HDAC inhibitors can disrupt the class IIa HDAC corepressor complex by changing the conformation of the class IIa HDAC active site, which mediates physical association with N-Cor/SMRT (Hudson et al, 2015;Lahm et al, 2007). Therefore, HDAC inhibitors that were thought to only inhibit class I HDAC catalytic activity may have efficacy against class IIa HDAC transcriptional repression.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies using various HDAC inhibitors have reported similar enhancements in various aspects of muscle and whole-body metabolism, including insulin sensitivity (Tan et al 2015) and enhanced oxidative capacity (Galmozzi et al 2013). The exact mechanism of action of some of these broad-spectrum HDAC inhibitors remains to be determined, but could include inhibition of HDAC3, the class I HDAC that provides deacetylase activity to the class IIa HDAC corepressor complex (Fischle et al 2002;Hudson et al 2015). Systemic administration of these inhibitors could have compound-specific effects in tissues other than skeletal muscle.…”
Section: Epigenetic Therapies To Induce Exercise Adaptationsmentioning
confidence: 97%